Acupuncture Regulates Symptoms of Parkinson’s Disease via Brain Neural Activity and Functional Connectivity in Mice - Oh, Ju-Young; Lee, Ye-Seul; Hwang, Tae-Yeon; Cho, Seong-Jin; Jang, Jae-Hwan; Ryu, Yeonhee; Park, Hi-Joon (Frontiers in Aging Neuroscience, 2022)
Parkinson’s disease (PD) is a multilayered progressive brain disease characterized by motor dysfunction and a variety of other symptoms. Although acupuncture has been used to ameliorate various symptoms of neurodegenerative disorders, including PD, the underlying mechanisms are unclear. Here, we investigated the mechanism of acupuncture by revealing the effects of acupuncture treatment on brain neural responses and its functional connectivity in an animal model of PD. We observed that neuronal dysfunction between many brain regions in PD reversed functional connectivity as the number of nodes increased after acupuncture treatment. Using machine learning analysis, we found that the brain region most altered by acupuncture was the primary motor cortex (M1), and this region also showed a significant correlation with motor behavior. In addition, acupuncture treatment was shown to significantly normalize the brain neural activity not only in M1 but also in other brain regions related to motor behavior (striatum, substantia nigra pars compacta, and globus pallidus) and non-motor symptoms (hippocampus, lateral hypothalamus, and solitary tract) of PD. Together, our results demonstrate a close coupling between brain neural activity and functional connectivity following acupuncture treatment in a PD animal model and provide new insights that enhance our current understanding of acupuncture mechanisms for non-motor symptoms.